Orange the complete collection / Volume 2 - Takano, Ichigo, 1986-; Tamosaitis, Amber; Fay, Shannon (2016)
Orange: The Complete Collection is a romantic comedy manga series by shoujo author and artist Ichigo Takano. This critically-lauded manga series will tug at your heartstrings with its central plot device about time travel and communication with a future self.
Reads from left to right
Rated: Teen
Translated from the Japanese
Keywords: Fate and fatalism -- Comic books, strips, etc; High school students -- Comic books, strips, etc